Comparing surface immune markers in successful and non-viable ART pregnancies on the day of hCG measurement: a prospective pilot study - Kevin Marron; Conor Harrity (Reproduction and Fertility)
Blood lymphocyte reference ranges in non-pregnant females are established, but changes in pregnancy are less well understood. The early identification of immunological markers that could suggest an increased risk of early pregnancy loss may allow for timely intervention to improve outcomes. A lymphocytic immunophenotype provides a broad assessment of important immune parameters and potential indicators, which may be of relevance to pregnancy outcome. Comparison of immunophenotype results on the day of a positive hCG after embryo transfer between successful and failed pregnancies allows for this assessment. Baseline non-pregnant lymphocyte percentage and cell/µL profiles were established with a comprehensive panel on 93 age-matched male factor controls. Sixty-five in-vitro fertilisation (IVF) patients had an immunophenotype assessment on the day of a positive hCG, followed by further hCG tests and ultrasound monitoring as required to ultimately evaluate success (live birth) or failure (miscarriage). Thirty-one pregnancies were viable, leading to a live birth, while 34 ended in miscarriage. Total CD56, pNK, NKT, CD4 and CD8 levels were equivalent between all groups. Regardless of the outcome, B lymphocytes increased in pregnancy compared to controls. Of interest, in the later miscarriage cohort, pNK-specific CD69 was reduced (1.6 vs 5.4%, P = 0.02), while CD57+ cells were increased (45.4 vs 38.9%, P = 0.025). Corresponding changes were observed in cell/µL concentrations. Low level CD69 activation and elevated CD56dim and CD57+ NK cells were identified as markers that could potentially identify a pregnancy at risk of miscarriage, with further study needed to explore whether these changes represent cause or effect.